Skipping your workout, again? Measuring and understanding time inconsistency in physical activity - Diarmaid Ó Ceallaigh; Kirsten I. M. Rohde; Hans Van Kippersluis (Tinbergen Institute, 2024)
Anecdotally, physical activity appears to be a textbook example of time inconsistency, which is the failure to follow through on ex-ante preferences and plans. Interestingly, our longitudinal survey finds that, over a fortnight, exercising more than preferred/planned is actually more prevalent than exercising less. However, over time a majority of our sample exercise less than preferred/planned in at least one of two consecutive fortnights. We find little evidence that time inconsistency is associated with present bias, its most popular explanation in economics. We find instead that it is associated with time-varying affective psychological processes such as willpower and temptations.
Keywords: C21; D91; I12; 330